22.4k views
3 votes
hi I am working on an assignment and i came up on a question that I did not understand please help me understand and answer this please

hi I am working on an assignment and i came up on a question that I did not understand-example-1
User Jkm
by
4.8k points

1 Answer

1 vote

Solution

Step 1:

Write the two equations:

2x + 3y = 12

2x + y = 6

2x = 6 - y


\begin{gathered} 6\text{ - y + 3y = 12} \\ 2y\text{ = 12 - 6} \\ \\ 2y\text{ = 6} \\ \\ y\text{ = 3} \end{gathered}

Answer

The first step in solving by substitution would be to solve the second equation for x, since the coefficient is 2.

First

y = 6 - 2x

y = 3

User Qpingu
by
4.8k points